The Use of Adipose-Derived Mesenchymal Stem Cells in the Treatment of Claw Lesions in Cows - Nataly Kostyuk; Andrei Prytychenka (Journal of Global Innovations in Agricultural Sciences)
The treatment of claw lesions in cattle is one of the most pressing aspects of veterinary surgery. The main options of treatment include claw trimming along with various methods to speed up healing. At the same time, the problem of finding new agents to improve tissue regeneration remains. Mesenchymal stem cells (MSCs) cells may be considered as such a remedy. To evaluate the ability of bovine MSCs from adipose tissue (AT-MSCs) when used after claw trimming to heal the ulcers of digital caushion in the heel area (Ulcus Pulvinus Digitalis) or postoperative wounds after excision of interdigital hyperplasia (tyloma) in dairy cows. The experimental and comparison groups included 5 cows with ulcers and 5 with tylomas each. All the animals underwent claw trimming with primary surgical treatment including the tyloma excision. Then, cows in experimental group were once injected with a cell transplant into the skin area of the fornix of the interdigital cleft. The cows in comparison group received a single intramuscular injection of antibiotic and topical treatment of lesions with a spray. The therapy outcomes were assessed in dynamics of the wound healing and general condition. AT-MSCs at a dose of 5×106 cells in 2 ml in the case of ulcers and 107cells in 4 ml of saline solution in the case of tylomas shortens the wound healing period by (7.0 ± 2.1, P< .05) days as compared to the treatment with antibiotic and topical spray. The mesenchymal stem cells-based therapy may be used for wound healing in cow hooves. Keywords: Adipose tissue, claws and hooves, dairy cow, mesenchymal stem cells, wound healing.